Participatory And Social Financing From The Perspective Of Islamic Moral Economy - Fuady, Khairul; Juliandi, Budi; Muhammaddiah, Muhammad Rusdi Bin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research explores the intersection of participatory and social financing within the framework of Islamic Moral Economy (IME). The study delves into the nature of participatory and collaborative Islamic finance instruments and their alignment with the principles of IME. It also investigates the concept of Islamic social finance and its relationship with the idea of welfare in the context of IME. The paper further examines contemporary approaches to institutional adaptation in Islamic finance, focusing on how these approaches integrate participatory and social financing principles. Qualitative methodology By employing a rigorous literature review and in-depth analysis is utilized to gain insights into the practices and implementations of Islamic financial institutions in Indonesia. The findings shed light on the significance of the framework of Islamic Moral Economy in Islamic financial practices and its potential for promoting financial inclusion and socio-economic welfare to develop moral and community-centered financial models